Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration mothers and some supply meals other than milk. There is wide variation in the methods of determining in what circumstances milk and meals shall be granted. Section 84 of the Education Act (1921) permits Education Authorities to give free meals to all children who are unable by reason of lack of food to take full advantage of the education provided for them. The clause is permissive, and while it has been adopted by most Authorities it has not really been used. It has been quite common to have a rule that children can be fed only when the doctor reports definite symptoms of malnutrition. In the autumn of 1934 the Government issued instructions (Circular 1437) that this bad rule must become the practice of all Authorities. As a result of widespread protests Circular 1444 was issued in December, 1935, modifying the cruel and stupid policy of “a trial period of starvation” laid down a year earlier. In March of this year 233 Authorities in England and Wales were providing meals, but this includes the Authorities which give free milk only. There are still 83 Authorities which make no free provision of milk or meals. It is clear from available figures that in most cases milk only is given. In December last out of a total of 322,878 children in England and Wales who were receiving free meals and milk, 233,257 received milk only, and 89,621 received meals —and of these 42,359 received milk as well as meals. These figures show that the School Meals Clause is being used very inadequately. While the number of Authorities providing meals increased from the year 1933-34 to 1934-35, the number of individual children fed decreased and also the total number of meals provided. In many areas Public Assistance Committees in assessing the means of applicants for transitional payment took into account the value of meals provided at school, so that mothers had often to choose between school meals and a little extra money. The Government refused to issue any instruction to Local Authorities to ignore school 18 127/NU/5/5/1/12